Implementation of Community Empowerment in Thematic Programs in Tidar Village, Tangerang City - Talakua, Decky Carste (International Publisher, 2024)
The environmental problems we are experiencing now are a matter of healthy survival, harmony with nature and the continuation of peaceful life for generations. In reality, the pace of development does not seem to be able to escape environmental pollution, so that the earth's carrying capacity is increasingly decreasing. One of the Tangerang City government's innovations in overcoming the problem of slum settlements is through the